Penguatan Strategi Pendidikan Tauhid dan Anti-Syirik dalam Surah Āli ‘Imrān: Kajian Tafsir Tematik - Suyuti, Achmad Wildan (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the values of tawḥīd and anti-shirk corrections in Surah Āli ‘Imrān thematically and to formulate applicable ‘aqīdah education strategies in the modern context. Employing a qualitative approach with the thematic exegesis (tafsīr mawḍū‘ī) method, the research compiles verses related to rubūbiyyah, ulūhiyyah, asmāʾ wa ṣifāt, and warnings against shirk, then analyzes them based on classical exegesis (Ibn Kathīr, al-Ṭabarī, al-Baghawī) and contemporary interpretations (al-Misbah). Data were collected through library research and analyzed using thematic content analysis. The findings identify three main subthemes: (1) steadfastness of faith and Islamic brotherhood (verses 102–104); (2) family-based education as a medium for ‘aqīdah transmission (verses 33–37); and (3) strengthening faith through reflection on Allah’s creation (verses 190–200). Comparative analysis reveals consistency with previous studies while offering a novel contribution in the form of an implementable tawḥīd education model integrating cognitive, affective, and psychomotor learning domains. Theoretically, the study underscores the importance of thematic exegesis as a bridge between Qur’ānic text and ‘aqīdah curriculum design.